PENGARUH PEMBERIAN AIR JAHE TERHADAP PENURUNAN NYERI DISMENORE (Jurnal Kesehatan Siliwangi, 2022)
In Indonesia, the incidence of dysmenorrhea is 64.25%, consisting of 54.89% having primary dysmenorrhea and 9.36% suffering from secondary dysmenorrhea. Dysmenorrhea is abdominal pain that comes from uterine cramps and occurs during menstruation (Morgan, 2009). One of the management of non-pharmacological therapy to reduce pain during menstruation is by giving herbal ingredients, namely ginger water. This is in line with research which states that ginger has the same effectiveness as mefenamic acid and ibuprofen in reducing primary dysmenorrhea pain. This evidence based case report is to find out the evidence based on giving ginger water to dysmenorrhea in women of childbearing age. Search articles regarding the effect of giving ginger water on reducing dysmenorrhoea pain were carried out in e-data based Pubmed and Schooler, so that 3 articles were obtained with 2 Quasi Experimental Design research designs and 1 Meta-Analysis and Systematic Review and met the inclusion criteria that had been previously determined, then A review of the journal was conducted, and it was found that the administration of ginger water affected the reduction of dysmenorrhoea pain and could be applied to patients.